Violência conjugal: mapeando e compreendendo o fenômeno - Rosa, Larissa Wolff da (Universidade do Vale do Rio dos Sinos, 2013)
Conjugal violence is a high complex phenomenon that demands many views to become more understandable. This essay has as proposal to map the conjugal violence in Rio Grande do Sul and understand the mechanisms of violent situations of couples. In this proposal two researches were performed. The first one was qualitative. It was part of a bigger Project entitled “Mapeamento e intervenção nas relações conjugais no Rio Grande do Sul” (Edital Pronex/Fapergs/CNPq). This research had the participation of 751 couples, among 18 and 80 years old, of different geographical areas. For this essay was analyzed socio-demographic data and Conflict Tactics Scale (CTS2) data. The mainly results of the analysis showed that education, income, time of relationship and conjugal situation are directly involved in the levels of conjugal violence in its different dimensions (p<0,05), as they showed the existence of mutual and symmetrical aggressions between couples. The second stage had as objective understand the mechanisms of violent situations of couples, and it was qualitative, taking many cases as a framework. Three couples, selected in the first step, participated in a semi-structured interview and after established narratives about the cases. The results showed that violence was present in different ways (physical, sexual and psychological) in the analyzed couples been execute by both of spouse. It was noted the existence of a conjugal template that favored the maintenance of violence in their relationships, settling the necessity of reflect about the psychological support with couples in a violent situations.
Keywords: Violência conjugal; Relações homem-mulher; Aspectos psicológicos; Crime sexual; ACCNPQ::Ciências Humanas::Psicologia